UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN DAN KULIT BATANG KALANGKALA (Litsea angulata) ASAL KALIMANTAN SELATAN - Eka Fitri Susiani; Revita Saputri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Antioxidants have an important role in inhibiting free radicals that trigger oxidative stress cells that cause degenerative diseases. Kalangkala (Litsea angulata) is a typical plant of Borneo which may have antioxidant activity. This study aims to determine the antioxidant activity of ethanol extract of leaves and stem bark of Kalangkala (L.angulata) from South Borneo. Extracts were investigated for antioxidant activity qualitatively and quantitatively using 2,2-diphenyl-1-picrylhydrazyl (DPPH). Qualitatively, the results of antioxidant assays from ethanol extract of leaves and stem bark showed that there were yellow spots with a purple background on the TLC plate. Quantitatively, the ethanol extract of Kalangkala leaves obtained IC50 values of 152.39 ppm, while the ethanol extract of Kalangkala stem bark obtained IC50 values of 85.33 ppm. Thus, it can be concluded that the leaves and stem bark of Kalangkala (L.angulata) have antioxidant activity.